Pengetahuan dan Pola Asuh Ibu Sebagai Faktor Keberhasilan Toilet Training Pada Anak Usia Prasekolah di PAUD Klampis Kabupaten Bangkalan Madura - Zufra Inayah; Wiwik Widiyawati; Diyah Fauziyah; Tri Nova (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
Toilet training aims to train children to be able to control bowel movements and urination. Based on preliminary data 70% of children do not succeed in toilet training. Children will grow and develop optimally if their parents understand how to do parenting regardingdevelopment of child. This study aimed to determine the mother's knowledge and parenting towards the success of toilet training.This study using observational and cross sectional design. Population were parents who have preschool age children (3-4 years) as many as 50 people, sampling was done by cluster random sampling with a total of 45 people. Data were collected using a questionnaire and analyzed using the Lambda Contingency Coefficient test.Results showed 34 people (75.6%), mothers had good knowledge, 29 people (64.4%) mothers used democratic parenting and 27 people (60%) children who successfully carry out toilet training. The Lambda Contingency Coefficient test correlation between the level of maternal knowledge and the success of toilet training in preschool children in PAUD Klampis had p value = 0.036 <0.05 and the relationship between maternal parenting and the success of toilet training in preschoolers in Klampis PAUD had p values = 0.007 <0.05.There was a relationship between the level of mother's knowledge and parenting with the success of toilet training in preschool children in PAUD Klampis, Bangkalan  RegrencyKeywords: Knowledge, Parenting, Toilet Training, Preschool